Comparative Efficacy of Different Covers Against Bird Damage and Their Effects on Berry Characteristics in Date Palm - Swaminathan, R; Verma, S K (Annals of Arid Zone, 2016)
Rose-ringed parakeet. house sparrow, bulbul and crows are major bird pests of date palm in arid western Rajasthan. Various covers were evaluated to protect the berries from bird damage. Nylon net (19-mmZmesh) afforded the maximum protection to benies but ware the most costly. By their bsneficial effects on fruit quality and high benefit to cost ratio, polyethylene bags, followed by gunny bags. proved to be better. Wire gauge coverings were difficult to handle in the effort to avoid mechanical injury 10 berries. Paper bags were not satisfactory on account of poor stability under wind or showers.